Electrochemical Investigation of DNA Interactions with Cyanobacterial Toxins: Cylindrospermopsin and Saxitoxin - Kesici-Meco, Ece; Yilmaz, Mete; Unur-Yilmaz, Ece (Wiley-V C H Verlag Gmbh, 2025)
Anthropogenic eutrophication threatens freshwater sources used for agricultural irrigation and increases the occurrence risk of cyanotoxins, such as cylindrospermopsin (CYN) and saxitoxin (STX). These toxins accumulate in surface waters and pose significant health risks, with CYN primarily affecting the liver and STX targeting the nervous system. In this study, dsDNA was immobilized on a pencil graphite electrode (PGE), and its interactions with CYN and STX were investigated by means of electrochemical impedance spectroscopy (EIS). Experimental conditions, including DNA concentration, cyanotoxin concentration, and DNA-cyanotoxin interaction time, were optimized to generate the most significant electrochemical signal (i.e., charge transfer resistance). The optimized PGE/DNA system established the foundation for an electrochemical biosensor that can be utilized for detection of cyanotoxins and detection limits of 0.12 ng mL-1 and 0.043 ng mL-1 were achieved for CYN and STX, respectively. The system was further analyzed using FTIR, UV-vis, and X-ray photoelectron spectroscopy (XPS), providing a comprehensive structural analysis of toxin-induced DNA alterations. The electrochemical system developed in this study by immobilizing DNA onto PGE allowed thorough investigation of the genotoxic effects of CYN and STX, as well as their sensitive detection.
Keywords: Cylindrospermopsin; DNA; Electrochemical biosensors; Pencil graphite electrode; Saxitoxin